Ler e compartilhar na web: práticas informacionais de blogueiros literários - Jessica Patricia Silva de Sa (2018)
Readers of literature, among other alternatives, can share their reading experiences by inserting themselves in a virtual environment and searching for other readers on the web. This thesis aims at investigating literary blogs in order to examine the information practices of bloggers with respect to their roles as readers, content producers, and reading mediators in the webrings, the social circles of bloggers, belonging to the literary blogosphere. It is believed that the understanding of informational practices of these subjects can provide important elements for understanding the ways in which social circles deal with information in blogs available on the web. The social approach to the studies of information users was adopted as theoretical support based on the concept of information practices as a way of understanding the relationship between subject and information. A review of theory was carried out regarding blogs, highlighting the meaning of webrings as social circles formed by bloggers in the web. Literary reading was discussed with emphasis on its appropriation and sharing. Since the research was qualitative and in depth, the methodology involved the use of netnography, which allowed an immersion in the literary blogosphere, using the documentary analysis and the semi-structured interview as data collection techniques. The data obtained were evaluated based on the content analysis and discussed in light of the theoretical support. The results pointed out the information practices performed by the eight bloggers identified in the sample, which were listed in four categories: reading, identity, information actions, and interaction. Regarding the roles played by the bloggers in the literary blogosphere, it was identified that they act as readers and as content producers but are not considered mediators of reading, although they encourage reading on their blogs. The motivation of each blogger both to enter the literary blogosphere and to keep their blog active runs through personal matters that extend beyond the simple desire to share readings: the need to overcome shyness, to have an active voice, and to be heard by other people, as well as being able to express their own opinion about the readings, set an example for their children and keep them close, escape from loneliness, and the responsibility for editorial partnerships and blog readers. Regarding the formation of webrings, it was verified that they are formed both in virtual and in person, through literary events. However, the interaction between literary bloggers occurs predominantly in the virtual environment. Keywords: Information